(untitled) (Research, Society and Development, 2022)
In the current scenario, pregnancy is a process that is part of the lives of many women, however, early pregnancy can harm the health of the adolescent and her family, considering that it is considered a public and social health problem, as the adolescence and a period of physical, psychological, hormonal and discovery transformations, sex education should be started as soon as possible, being assumed by parents, and complemented by school and health professionals, the nurse has an essential role in the development of skills. prevention and education with adolescents. This study has as general objective to analyze the work of nurses in preventing teenage pregnancy. This is a literature review, which aims to analyze the work of nurses in preventing teenage pregnancy. After the reflective reading of the articles, two categories emerged: Nurse actions to help prevent teenage pregnancy and nurses’ guidance in raising awareness of the prevention of teenage pregnancy. For sample selection, there was a time frame from 2015 to 2020, as the study captured publications from the last 5 years. It is concluded that this study showed that nurses in primary care are essential to implement actions establishing strategies aimed at preventing teenage pregnancy.